(–)-Epigallocatechin-3-gallate attenuated myocardial mitochondrial dysfunction and autophagy in diabetic Goto–Kakizaki rats. (August 2014) - Liu, J.; Tang, Y.; Feng, Z.; Liu, J.; Liu, J.; Long, J.
Abstract Type 2 diabetes mellitus (T2DM) is a risk factor for heart disease. However, the mechanisms of T2DM involvement in cardiac complications are still unclear. In the present study, we investigated mitochondria-related mechanisms underlying the pathogenesis of myocardial disorders in diabetic Goto–Kakizaki (GK) rats. We found that remarkable myocardial mitochondrial deficiency and dysfunction as well as oxidative stress occurred in the heart of GK rats. In addition, our results suggested that the loss of mitochondria was in response to elevated autophagy and upstream FoxO factors in diabetic myocardium. More importantly, (–)-epigallocatechin-3-gallate (EGCG), a polyphenol derived from green tea, successfully improved mitochondrial function and autophagy in the heart of GK rats. Our findings revealed that diabetes-associated myocardial mitochondrial deficiency and dysfunction was associated with enhanced autophagy in myocardium, and EGCG might be a potential agent in preventing and treating myocardial disorders involved in diabetes.